A dynamic dispatching control system for processing workshop based on multi-agent and value matching. (January 2023) - Zhang, Zequn; Tang, Dunbing; Zhu, Haihua; Wang, Liping; Nie, Qingwei
In the current manufacturing environment, orders began to show trends in small batches and multiple varieties. Production workshops are expected to be more flexible and agile. This paper proposes a dynamic control system for the processing workshop based on the multi-agent architecture. The workshop layer is divided into multiple "processing cells" according to function. Machine agents and part agents are designed to achieve distributed control. In this paper, disturbances caused by random tasks to production are considered. A dynamic task dispatching mechanism based on the scrolling time window is investigated. When dispatching events occur, the machine agents and part agents determine the connection value between them through negotiation. An arbitration agent is designed to implement the dispatching through value matching. Finally, an actual experiment is carried out to verify the effectiveness of this dynamic control system.